Los productores de plátano Orito y su aporte al desarrollo socioeconómico del cantón Caluma provincia Bolívar periodo 2017 - Yánez García, Carlos Luis (2018)
The research work "The producers of plantain orito and its contribution to the socioeconomic development of Canton Caluma – Provincia Bolívar-period 2.017"; It is directly related to the career of commercial engineering and allowed to know about the easy production of orito without chemicals due to the privileged geographical position in which it is located, reaching 40,800 boxes of gold per month, same that are sold to intermediaries at prices less than the official; the extension of the agricultural frontier, since before the orito was not cultivated in that zone and today it reaches 200 Has of extension; the generation of new sources of work mostly for people from the Canton of Caluma and even for people from outside, the same ones that currently reach 1,500 workers; the process of commercialization with intermediaries who do not pay the official price and who then sell to exporters, earning profits easily; and, finally, these abroad; however, this contributes greatly to the socioeconomic development of Canton Caluma; since the producers buy on the site the tools, machines, seeds, fertilizers and inputs, which stimulates the economy of the place. In order to make the change of the production matrix a reality and to promote its production of orito in the Canton of Caluma, it is necessary the state support with technical advice, credit, fertilizers and supplies; in addition, that the payment of the fair price per box of orito is fulfilled by the intermediaries and that the sale is made directly from the producer. The production of orito has a good future because of the geographical situation, the quality of the land, the climate and its hardworking people; However, the changes mentioned above are needed, as well as the participation of marketing specialists to carry out direct negotiation between producers and exporters, eliminating middlemen who are the ones who obtain easy profits without doing almost anything.